The Many Faces of Part-List Cuing—Evidence for the Interplay Between Detrimental and Beneficial Mechanisms - Lehmer, Eva-Maria; Bäuml, Karl-Heinz T. (Frontiers in Psychology, 2018)
If participants study a list of items and, at test, receive a random selection of the studied items as retrieval cues, then such cuing often impairs recall of the remaining items. This effect, referred to as part-list cuing impairment, is a well-established finding in memory research that, over the years, has been attributed to quite different cognitive mechanisms. Here, we provide a review of more recent developments in research on part-list cuing. These developments (i) suggest a new view on part-list cuing impairment and a critical role of encoding for the effect, (ii) identify conditions in which part-list cuing impairment can turn into part-list cuing facilitation, and (iii) relate research on part-list cuing to a phenomenon from social memory, known as collaborative inhibition. The recent developments also include a new multi-mechanisms account, which attributes the effects of cuing to the interplay between detrimental mechanisms -- like blocking, inhibition, or strategy disruption -- and beneficial mechanisms -- like context reactivation. The account provides a useful theoretical framework to describe both older and newer findings. It may guide future work on part-list cuing and may also motivate new research on collaborative inhibition.